Basura [videorecording] saw it coming ... - Severino, Howie; Philippine Center for Investigative Journalism; I-Witness. (Quezon City GMA News and Public Affairs, 1999)
Garbage is not a simple problem. for metropolis of 10 million people, it has become an environmental, political and economic issue.
First broadcast on GMA-&'s I-Witness on August 30, 1999
Line Producer: Howie Severino, Reporter/Scripwriter: owen Santos
Keywords: Garbage; Scavengers